2018
DOI: 10.1080/19932820.2018.1479602
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt consumption and the knowledge, attitudes and behavior of healthy adults: a cross-sectional study from Jordan

Abstract: High dietary sodium is recognized as a silent killer responsible for 2.3 million deaths worldwide in 2010 predominantly secondary to hypertension and its complications. Although high salt consumption is considered a worldwide public health problem, its magnitude is highly variable among different communities; therefore, it is important to study locally. This study aimed to evaluate habitual salt consumption, its important correlations, as well as the knowledge, attitude, and behavior of healthy Jordanian citiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…Similar findings were noted in a Jordan study using 24-h urinary sodium excretion, which showed that the average sodium intake was 4100 mg/day (10.4 g/day salt) and sodium intake was higher in males, 4300 mg, compared with 4000 mg by females. It was clear that the Jordanian participants consumed at least double the current WHO recommended daily sodium amount of 2000 mg (5 g salt) [27]. Likewise, a study conducted in Oman using the National Nutrition Survey based on a 24-h dietary recall noted the average intake of salt to be 11-12 g/day [28], again significantly higher than the WHO recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were noted in a Jordan study using 24-h urinary sodium excretion, which showed that the average sodium intake was 4100 mg/day (10.4 g/day salt) and sodium intake was higher in males, 4300 mg, compared with 4000 mg by females. It was clear that the Jordanian participants consumed at least double the current WHO recommended daily sodium amount of 2000 mg (5 g salt) [27]. Likewise, a study conducted in Oman using the National Nutrition Survey based on a 24-h dietary recall noted the average intake of salt to be 11-12 g/day [28], again significantly higher than the WHO recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension is still increasing in most parts of the world. It is estimated that this disease is growing in developing countries [ 8 , 9 ], especially Asia and the Middle East, mainly due to lifestyle, especially high-calorie diets, and the use of ready-made and salty foods [ 10 , 11 ]. According to Etaat et al, the study conducted in 2020, the leading cause of high blood pressure in Iran is obesity and high waist size [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as sex and awareness of the health consequences of excessive intake of sodium are also linked to excessive sodium intake [ 14 ]. Limited awareness of the health consequences of excessive sodium intake has been reported in a number of populations [ 2 , 15 ].…”
Section: Introductionmentioning
confidence: 99%